2021
DOI: 10.1101/2021.03.19.436090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited effects of m6A modification on mRNA partitioning into stress granules

Abstract: Recent studies have argued that the m6A modification of mRNAs promotes mRNA recruitment to stress granules through the interaction with YTHDF proteins (Anders et al., 2018; Ries et al., 2019). However, mRNAs that contain multiple m6A modified sites partition similarly into stress granules in both wild-type and m6A-deficient cells by single-molecule FISH suggesting m6A modifications play a minor role in mRNA partitioning into stress granules. Moreover, multiple linear regression analysis suggests m6A modificati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A recent study looked at methylated transcripts in control cells and "∆METTL3" mouse embryonic stem cells to examine the effect of m 6 A on mRNA enrichment in stress granules 42 . In this study, fluorescence in situ hybridization (FISH) showed that three m 6 A-containing mRNAs showed little difference in their stress granule enrichment levels in wild type or ∆METTL3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study looked at methylated transcripts in control cells and "∆METTL3" mouse embryonic stem cells to examine the effect of m 6 A on mRNA enrichment in stress granules 42 . In this study, fluorescence in situ hybridization (FISH) showed that three m 6 A-containing mRNAs showed little difference in their stress granule enrichment levels in wild type or ∆METTL3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that m 6 A on mRNAs promoted YTHDF1-3 partitioning into phase-separated structures ( Ries et al, 2019 ). However, a more recent study demonstrated that mRNAs, with or without m 6 A modifications, show minor differences in partitioning to stress granules and therefore argue that m 6 A may only play a minor role in stress granule partitioning ( Khong et al, 2021 ). The authors of this study hypothesize that it is not only m 6 A-YTHDF interactions that promote stress granule partitioning, but rather, there may be several other RNA-protein interactions outside of m 6 A-YTHDF that promote stress granule portioning ( Khong et al, 2021 ).…”
Section: The Role Of M 6 a In Diverse Cellular Fun...mentioning
confidence: 99%
“…Recent research, however, indicated that blocking the intracellular m 6 A modification process directly has almost no impact on the basic SG assembly procedure. 56 This suggests that the significance of m 6 A modification itself in regulating SG homeostasis still requires more exploration.…”
Section: Post-transcriptional Modifications Of Rnas Inmentioning
confidence: 99%
“…Intriguingly, knockout of YTHDF1 or YTHDF3 could interfere with SG assembly, while the interaction between YTHDFs and m 6 A-modified mRNAs can promote SG assembly. , These results not only suggest the importance of the YTHDF family in SG assembly but also point to a potential regulatory role for m 6 A modification in SG dynamics. Recent research, however, indicated that blocking the intracellular m 6 A modification process directly has almost no impact on the basic SG assembly procedure . This suggests that the significance of m 6 A modification itself in regulating SG homeostasis still requires more exploration.…”
Section: Physiological Regulation Of Sg Homeostasismentioning
confidence: 99%